El papel de las empresas de Hong Kong en las relaciones sino-latinoamericanas: la diplomacia portuaria de Li Ka-shing como ejemplo - Shen, Simon (El Colegio de México, 2013)
In recent years, Sino-Latin American relations have taken on a growing strategic importance that has surpassed commercial expectations. However, academic research often ignores civilian interactions in this regard. Hong Kong, as a Special Administrative Region with authority to conduct “external affairs”, functions as an ‘unofficial’ or ‘white glove’ diplomatic channel for Beijing, especially on issues sensitive to China. Thus, the article focuses on the role of Hong Kong tycoon Li Ka-shing's company in Latin America with the aim of analyzing the possible contributions and influence of its investments in the development of Sino-Latin American relations.